2016
DOI: 10.1111/jth.13289
|View full text |Cite
|
Sign up to set email alerts
|

Coronary or thoracic artery calcium score in provoked and unprovoked pulmonary embolism: a case‐control study

Abstract: To cite this article: van der Bijl N, Klok FA, Huisman MV, Roos de A, Kroft LJM. Coronary or thoracic artery calcium score in provoked and unprovoked pulmonary embolism: a case-control study. J Thromb Haemost 2016; 14: 931-5. Essentials• Patients with unprovoked pulmonary embolism (PE) are at increased risk of arterial thromboembolism.• Coronary and thoracic aorta calcium were evaluated in patients with and without (unprovoked) PE.• No association was found between (unprovoked) PE and coronary or aortic calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This is similar to the frequency identified in previous cohorts. 26,27 After 3 years of follow-up, CAC and age were the only independent predictors of mortality. This suggests that if patients survive the early haemodynamic effects of PE and receive appropriate treatment, the subsequent prognosis depends more on comorbidities than the severity of the initial PE.…”
Section: Discussionmentioning
confidence: 96%
“…This is similar to the frequency identified in previous cohorts. 26,27 After 3 years of follow-up, CAC and age were the only independent predictors of mortality. This suggests that if patients survive the early haemodynamic effects of PE and receive appropriate treatment, the subsequent prognosis depends more on comorbidities than the severity of the initial PE.…”
Section: Discussionmentioning
confidence: 96%
“…Our study is one of the few in the literature to evaluate coronary artery atherosclerosis in PE patients 6–10 . This retrospective study investigated the ability of CTPA to establish a PE diagnosis, simultaneously assess RVD and CAC, and predict severe clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calcification was present in 148 (44.8%) patients, which means that coronary artery atherosclerosis is common among patients with PE. Previous studies have reported frequencies of CAC ranging from 44% to 68% 6–10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAC was estimated using an ordinal visual scale by a cardiothoracic imaging radiologist with 10 years of experience, blinded to the outcomes. This method was originally described and validated by Shemesh et al 14 on nongated low-dose CT lung cancer screening studies, has been previously applied in contrast and noncontrast ECG-gated and non-ECG-gated studies, 13,[21][22][23] can be performed on standard images with no additional reconstructions performed, and found to have high interobserver reproducibility and strong agreement with gold standard Agatston scoring. 24 Left main, left anterior descending, circumflex, and right main were considered as 4 main coronary arteries on CTPA.…”
Section: Ordinal Assessment Of Cacmentioning
confidence: 99%